Assessing the Challenges in the Application of Potential Probiotic Lactic Acid Bacteria in the Large-Scale Fermentation of Spanish-Style Table Olives - Rodríguez-Gómez, Francisco; Romero-Gil, Verónica; Arroyo-López, Francisco N.; Roldán-Reyes, Juan C.; Torres-Gallardo, Rosa; Bautista-Gallego, Joaquín; García-García, Pedro; Garrido-Fernández, Antonio (Frontiers in Microbiology, 2017)
This work studies the inoculation conditions for allowing the survival/predominance of a potential probiotic strain (Lactobacillus pentosus TOMC-LAB2) when used as a starter culture in large-scale fermentations of green Spanish-style olives. The study was performed in two successive seasons (2011/2012 and 2012/2013), using about 150 tonnes of olives. Inoculation immediately after brining (to prevent wild initial microbiota growth) followed by re-inoculation 24h later (to improve competitiveness) was essential for inoculum predominance. Processing early in the season (September) showed a favourable effect on fermentation and strain predominance on olives (particularly when using acidified brines containing 25 L HCl/vessel) but caused the disappearance of the target strain from both brines and olives during the storage phase. On the contrary, processing in October slightly reduced the target strain predominance on olives (70-90%) but allowed longer survival. The type of inoculum used (laboratory vs. industry pre-adapted) never had significant effects. Thus, this investigation discloses key issues for the survival and predominance of starter cultures in large-scale industrial fermentations of green Spanish-style olives. Results can be of interest for producing probiotic table olives and open new research challenges on the causes of inoculum vanishing during the storage phase.